2016
DOI: 10.1016/j.atherosclerosis.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Plaque progression assessed by a novel semi-automated quantitative plaque software on coronary computed tomography angiography between diabetes and non-diabetes patients: A propensity-score matching study

Abstract: Plaque progression assessed by a novel semi-automated quantitative plaque software on coronary computed tomography angiography between diabetes and non-diabetes patients: A propensity-score matching study Methods: We identified 142 study subjects undergoing serial coronary computed tomography angiography. The resulting propensity score was applied 1:1 to match diabetic patients to non-diabetic patients for clinical risk factors, prior coronary stenting, coronary artery calcium (CAC) score and the serial scan i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 47 publications
3
29
0
1
Order By: Relevance
“…In contrast, CCTA can assess coronary artery plaque composition in a noninvasive manner. Several studies have revealed the potential of CCTA in quantifying plaque burden to quantify progression or regression of coronary artery disease . CCTA has been shown to accurately determine atherosclerotic plaque size, remodeling, and plaque morphology compared with IVUS as a reference standard .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, CCTA can assess coronary artery plaque composition in a noninvasive manner. Several studies have revealed the potential of CCTA in quantifying plaque burden to quantify progression or regression of coronary artery disease . CCTA has been shown to accurately determine atherosclerotic plaque size, remodeling, and plaque morphology compared with IVUS as a reference standard .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the potential of CCTA in quantifying plaque burden to quantify progression or regression of coronary artery disease. 18,36 CCTA has been shown to accurately determine atherosclerotic plaque size, remodeling, and plaque morphology compared with IVUS as a reference standard. 37 For quantitative atherosclerotic plaque analysis, we will use a semiautomated method with novel plaque-analysis software for the assessment of progression/regression of CAC and noncalcified plaques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial study sample size was estimated based on MDCTA data showing 24% ± 13% reduction in coronary artery plaque volume with moderate‐dose statin therapy . It is assumed that an 8% reduction in plaque volume (one‐third that seen with statin therapy) would be the minimally important change in noncalcified plaque volume based on past data; multiple studies have shown similar progression/regression rates with different therapies . Further data have been obtained using low‐attenuation plaque volume in both MDCTA and intravascular ultrasound (IVUS) studies.…”
Section: Methodsmentioning
confidence: 99%